Simple and fast analysis of iohexol in human serums using micro-hydrophilic interaction liquid chromatography with monolithic column - Thotsaphorn Chaloemsuwiwattanakan (2018)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A simple and rapid method based on micro-liquid chromatography using a synthetic monolithic capillary column was developed for determination of iohexol in human serums, a marker to evaluate the glomerular filtration rate. A hydrophilic methacrylic acid-ethylene dimethacrylate monolith provided excellent selectivity and efficiency for iohexol with separation time of 3 min using a mobile phase of 40:60 v/v 50 mM phosphate buffer pH 5/methanol. Four serum protein removal, methods using perchloric acid, 50% acetonitrile, 0.1 M zinc sulfate, and centrifuge membrane filter were examined. The method of zinc sulfate was chosen due to its simplicity, compatibility with the mobile phase system, nontoxicity, and low cost. Interday calibration curves were conducted over iohexol concentrations range of 2–500 mg/L (R2= 0.9997 ± 0.0001) with detection limit of 0.44 mg/L. Intra- and interday precisions for peak area and retention time were less than 2.8 and 1.4%, respectively. The method was successfully applied to serum samples with percent recoveries from 102 to 104. The method was applied to monitor released iohexol from healthy subject. Compared with the commercially available reversed-phase high-performance liquid chromatography method, the presented method provided simpler chromatogram, faster separation with higher separation efficiency and much lower sample and solvent consumption.